Process of EUR prediction for shale gas wells based on production decline models—a case study on the Changning block - Liu, Sha; Chang, Cheng; Xie, Weiyang; Li, Hong (Frontiers in Energy Research, 2023)
To effectively develop the shale gas in southern Sichuan Basin, it is essential to accurately predict and evaluate the single-well production and estimated ultimate recovery (EUR). Empirical production decline analysis is most widely used in predicting EUR, since it is simple and can quickly predict the gas well production. Nevertheless, it has disadvantages of several model parameters, large difficulty in fitting, and big deviation. This paper presents an efficient process of EUR prediction for gas wells based on production decline models. Application of 9 empirical production decline models (Arps, PLE, SEPD, DUONG, Wang, VDMA, HEMD, EEDCA and LGM) in more than 200 shale gas wells in Changning block of the Sichuan Basin was systemically analyzed. According to the diagnosis of flow regime, it is determined that all models are applicable in prediction of production and EUR in this area, with the fitting degree higher than 80% for gas wells producing for more than 12 months. Based on the fitting and prediction results, the parameter distribution charts of 9 production decline models with initial parameters constrained were plotted for shale gas wells, which greatly improve the prediction accuracy and efficiency. Coupling with the probability method, the EUR is evaluated and predicted effectively, and the average EUR of more than 200 shale gas wells in Changning block is 1.21×10 8 m 3 . The EUR of Well CNH1 predicted by the proposed process and charts is believed reliable. The study results provide a meaningful guidance for efficient prediction of gas well production and EUR in Changning block.